Reauthorizing No Child Left Behind: Facts and recommendations - Stecher, Brian M; Vernez, Georges (RAND, 2010)
Studies suggest that the No Child Left Behind Act of 2001's goal of 100 percent of U.S. students proficient in reading and mathematics by 2014 will not be met. The authors recommend more-uniform state academic standards and teacher requirements and broader measures of student learning, including more subjects and tests of higher-thinking and problem-solving skills.